Analysis of Adjacency Pairs of Mohammed’s Interview - Khalaf, Wisal; Sameer , Emad (Al-Adab Journal, 2023)
Conversation is a vital tool in communication for communicating meaningful pieces of interactions. Adjacency pairs are often seen as fundamental units in conversational organization. The form and purpose of a specific pair component, as well as the context beside the stage of the conversation, all play essential roles in determining the meaning and function of an utterance. Each pair has special intended meaning, purpose and function which cannot be fully understood without relying on the context at which the adjacency pairs appear. The present study tends to focus on adjacency pairs within sports interviews with the aim of studying these pairs pragmatically since defining the underlying expectations on which the regularities are founded is difficult. The study also aims at examining the adjacency pairs included in the exchanges between the TV interviewers as well as the footballers, finding out the communicative purposes behind the adjacency pairs usage that the player wishes to transmit when being interviewed. The method used for analysis is a mixed one (quantitative and qualitative) to analyze the latest interview for the player. The qualitative analysis examines the content of the utterances descriptively and the quantitative analysis relies on a table, under the interview, that shows the rates of the types of adjacency pairs. So, the selected interview is analyzed in terms of number, types, frequency and distribution of adjacency pairs. The adopted model is an eclectic one which composes Cook’s (1989) model of Adjacency Pairs, Van Dijk’s (2006) model of Context and Grice’s (1975) model of Cooperative Principles.